Boon or Bane? Advance Tax Rulings as a Measure to Mitigate Tax Uncertainty and Foster Investment. Issue 3 (3rd July 2017) - Diller, Markus; Kortebusch, Pia; Schneider, Georg; Sureth-Sloane, Caren
Abstract : Politicians and tax practitioners often claim that tax uncertainty negatively affects investment. In many countries, firms can request fee-based advance tax rulings (ATRs) to mitigate tax uncertainty. We analyse theoretically the circumstances under which investors request ATRs, how tax authorities should price them and how they can affect investment. We assume that tax authorities integrate investors' reasoning into their decisions. We find that in special cases the optimal fee tax authorities should charge is prohibitively high, thus firms will refrain from requesting ATRs. However, we find that revenue-maximising tax authorities offer ATRs if the ruling enables them either to significantly reduce their tax audit costs or to increase the probability of detecting ambiguous tax issues. Under certain circumstances, ATRs may effectively foster investment and potentially benefit both the tax authorities and taxpayers. Our results provide new explanations for why taxpayers that face high levels of tax uncertainty often do not request ATRs, even when the fee is rather low. Our results also hold when the tax authority maximises social wealth instead of its revenues. Regulatory changes in ATR requirements might serve as a natural quasi-experiment for an empirical study of our predictions regarding investment decisions.